HomeSoS: a conceptual framework to support system of systems management - Vargas, Iohan Gonçalves (2024)
Context: The knowledge required to manage software projects grows as complexity and integration efforts increase. In this context, Systems Engineering (SE) and Project Management (PM) teams must enhance their collaboration as they engage in large-scale projects. This relationship becomes even more complex in System of Systems Engineering (SoSE), where various constituent systems (CS) must collaborate to achieve a unified objective. In a System of Systems (SoS), individual systems are designed independently, then identified, chosen, integrated, and overseen to create a larger, more complex system. SoSE presents numerous challenges and remains an active area of research. Specifically, the management of SoS reveals several research gaps, particularly concerning authority and responsibility. Objective: This PhD thesis described the state-of-the-art management of SoS and presented a conceptual framework for managing SoS capabilities, named as HomeSoS. An SoS management framework is important to improve system management effectiveness and efficiency at both the SoS level and CS level. Method: In this scenario, we systematically developed and evaluated the HomeSoS through the Design Science methodology. Two evaluation studies, a Form-based questionnaire, and the analysis of existing SoS documentation were performed to show the suitability and utilization of Home- SoS in the SoS context. Results: Our work provided an overview of the SoS Management area and presented a holistic view framework to support SoS Management. While the traditional management approaches have focused on individual systems and processes, an integrative framework to manage multiple systems and their dynamic behaviors is needed. Conclusion: This PhD thesis can be seen as a starting point toward the Management of SoS capabilities. The solutions derived from HomeSoS serve as a guide to manage SoS classified as directed or acknowledged. By using SoS concepts, we can facilitate the creation of management tools and techniques that consider emergent properties and uncertainties. As a result, we intend with this framework to open new perspectives of research, promoting better cooperation and communication based on valuable insights into the SoS Management community.